Effects of bending on a flexible metamaterial absorber - Siti Nurzulaiha Isa; Osman Ayop; Abu Sahmah Mohd Supa’at; Mohammad Kamal A. Rahim; Noor Asniza Murad; Farid Zubir; Huda A. Majid (Bulletin of Electrical Engineering and Informatics, 2020)
This paper presents a study of bending a metamaterial based absorber. The study of bending is important for textile material since it can be easily crumpled. The basic absorber that is simulated for the study is an annulled circle as the top patch, and metal ground plane that sandwich a textile-based substrate. The center frequency for the absorber is 10.525 GHz. The type of bending is divided into two parts, which is convex bending and concave bending. Through series of simulations, the effects of the bending on the absorptivity and the shifting of the resonant frequency is observed. Also, the study on the change of incident and polarization angle is also included to support the basis of flexible metamaterial absorber affected by the bending.